(untitled) (Research, Society and Development, 2021)
This article presents a literature systematic review, analyzing how digital technologies are being adopted to help nurses that work in hospitals in the lifelong education perspective. The bases researched were IEEE explore, ACM Digital, Pubmed, Science Direct, Scopus and Willey. The Start tool was used to applied the protocol and to select the articles, through filters and five phases. The search was started with 738 articles, which were discarded according to the phases. Six international articles were select for complete reading and analysis. It was concluded that some technological tools are used in a superficial way and not developed for the purpose of training nurses that work in hospitals. The results identified research’s gap in the use of technologies in the nurses permanent training.